Proximal Row Carpectomy Using Decellularized Dermal Allograft: Preliminary Results - Lee, Steven J.; Rabinovich, Remy V.; Kim, Andrew (Journal of Wrist Surgery, 2020)
Objective The purpose of this study was to evaluate the short-term outcomes of patients undergoing proximal row carpectomy (PRC) with interposition arthroplasty using a decellularized dermal allograft.Methods Patients with a minimum of 1-year follow-up after undergoing a PRC using decellularized dermal allograft were contacted for clinical evaluation, radiographs, and postoperative outcome questionnaires, including the Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaire as well as the modified Likert scale for patient satisfaction. Nine of ten (90%) consecutive patients who were treated using this surgical technique were available for follow-up.Results At a mean follow-up of 18 months, a total of nine patients achieved a mean flexion-extension arc of 113 degrees, pronosupination of 170.5 degrees, grip strength of 68 Ibs and pinch strength of 17 Ibs. Relative to the contralateral side, these values were 95, 100, 84 and 82%, respectively. There was significant improvement in the mean DASH score from 63.5 preoperatively to 23.8 postoperatively. Patient satisfaction postoperatively achieved a mean modified Likert score of 1.5. There was no evidence of radiocarpal joint space degeneration or dislocation in any of the patients. No patient suffered wound-related issues, foreign-body reaction to the graft, or other complications.Conclusion PRC with interposition arthroplasty using a decellularized dermal allograft in patients with degenerative changes at the lunate fossa or capitate demonstrates short-term outcomes comparable to what has been reported for routine PRC in patients without degenerative changes affecting the radiocapitate joint. This method of interposition arthroplasty expands the indications for PRC and may help avoid salvage, motion-sacrificing procedures in select patients with late-stage wrist arthritis.Level of Evidence This is a level IV, therapeutic study.
Keywords: PRC; interposition arthroplasty; wrist arthritis; dermal allograft